In vitro antiproliferative activity of HT-29 and HL-60 cells, and proliferative activity of MSC treated with Channa striatus bloch crude extracts - Mohd Jamil, Nur Syamsyiah (2012)
Channa striatus (Haruan) has been traditionally used for wound healing especially for post-natal women and after surgery. It is scientifically proven to possess analgesic properties. Until today, the effectiveness of anticancer drugs is limited due to its toxicity to cancer cells as well as normal cells and bone marrow. The present study was carried out to determine the haruan crude extracts (Haruan traditional extract liquid phase [HTEA] and solid phase [HTES], haruan chloroform extract [HCE] and haruan methanol extract [HME]) in vitro cytotoxic activity on promyelocytic leukemia (HL-60) cells and colorectal adenocarcinoma (HT-29) cells and proliferative activity on mesenchymal stem (MSC) cells. The extracts were found to induce anti-proliferative effect on HL-60 and HT-29 cells and proliferative effect on MSC cells after tested using MT assay. HTES most effective to inhibit cell growth of HL-60 cells at 50% of cell population (IC50) values were 44.0 ± 0.37 μg/ml, 38.0 ± 0.52 μg/ml and 5.0 ± 0.83 μg/ml respectively, after treated for 24, 48 and 72 hours. HCE and HME also able to inhibit the growth of HL-60 cells which the IC50 values ranged from 78.0 ± 0.25 μg/ml at 48 hours up to 18.0 ± 0.32 μg/ml at 72 hours. However, only HME shows inhibition effect effectively against HT-29 which IC50 value was 78.0 ± 0.28 μg/ml at 72 hours. For comparative purposes, the IC50 values of several commercial anticancer drugs against HL-60 and HT-29 cells were tested. Doxorubicin was more significant to inhibit HL-60 cells with the IC50 was <5.0 ± 0.2 μg/ml at 24 hours of incubation period, while the 5-fluorouracil treated on HT-29 cells showed the IC50 values at 84.0 ± 0.19 μg/ml and 5.0 ± 0.71 μg/ml respectively, after 48 and 72 hours of incubation period. Interestingly, all extracts were found to induce proliferation of the MSC cells. HTEA shows the greatest value of cell proliferation which ranged from 115.4% ± 0.07 up to 148.0% ± 0.07 at 100 μg/ml. Furthermore, observation on morphological alterations indicating apoptosis was evaluated by using phase contrast and fluorescent microscopes. Analyses of AO/PI staining, DNA content and cell cycle have confirmed that the haruan crude extracts have ability in promoting apoptosis. However, the event is time-dependent. At the IC50 value, HTES, HCE and HME were able to induce apoptosis in HL-60 cells, and it also induced necrosis in HT-29 cells. Based on the results obtained, HTES, HCE and HME were found promoted better inhibitory effect compared to HTEA. As a result, this study demonstrated the antiproliferative activity of haruan crude HTEA, HTES, HCE and HME extracts against the HL-60 and HT-29 cell lines, as well as its ability to induce proliferation of MSC cells, which is in line with traditional claims that haruan promotes tissue growth.